Comparative Evaluation of Penetration of Various Nano-sized Intra-canal Medicaments: An In Vitro Confocal Laser Scanning Microscopic Study - Veeraiyan Mounika; Mastammanavar Deepa; Kavya Kantheti; Jarupula Deepa; Sairam Gangishetti (Wolters Kluwer Medknow Publications, 2024)
BackgroundTo assess and contrast the depth of penetration of conventional calcium hydroxide, nanoparticle calcium hydroxide, silver nanoparticles, and combination of nanoparticle calcium hydroxide and silver nanoparticles into dentinal tubules using confocal laser scanning microscope. Materials and MethodsEighty human single-rooted teeth were decoronated and instrumented up to Protaper Universal F3. Teeth were separated into four groups at random (n = 20) following chemomechanical preparation. Group 1: Control Conventional Calcium Hydroxide; Group 2: Nanoparticle Calcium Hydroxide; group 3: Silver Nanoparticles; group 4: Combination of Nanoparticle Calcium Hydroxide and Silver Nanoparticles. With the use of lentulo spirals, medications were injected into the canals, stirred up with ultrasound, and then kept at 37°C for 24 hours. A 1 mm thick slice was obtained at 5 mm from the root apex by sectioning the root perpendicular to the long axis of the tooth and then put on a glass slide to measure the depth of penetration using a confocal laser microscope. Statistical AnalysisTo quantify the depth of penetration among the four groups, a one-way ANOVA was used and post hoc-Tukey's test was used to compare between groups. ResultsAll of the groups were statistically significant, with group 4 showing the greatest depth of penetration, followed by group 2 and group 3. In contrast, all other groups in the intergroup comparison were statistically significant (P value 0.05) aside from the comparison of group 2 to group 3. ConclusionSilver nanoparticles and nanoparticle calcium hydroxide together demonstrated greater penetration than calcium hydroxide, silver nanoparticles, and nanoparticle calcium hydroxide alone.